Prevalence of Mycobacterium avium subsp. paratuberculosis and associated risk factors in dairies under mechanical milking parlor- systems in Antioquia, Colombia (2022)
ABSTRACT: The present study aimed to determine Mycobacterium avium subsp. paratuberculosis (MAP) prevalence according to environmental samples and to explore the herd-level risk factors associated to MAP infection in dairy herds under mechanical milking parlor and pasture grazing-based systems. The study herds (n= 94) were located in 60 districts from five municipalities in the Northern region of the province of Antioquia, Colombia. Herds were visited once in 2016 to collect two composite environmental samples and to complete a risk assessment questionnaire. MAP identification was carried out using a quantitative real-time PCR method based on the IS900 sequence. A herd was considered as MAP-positive if one or both of the environmental samples were found positive by the molecular technique. The information on risk factors was analyzed using a multivariable logistic regression model. The apparent herd-level prevalence found was 14.9 % (14/94; 95 % CI: 7.7-22.1), ranging from 0 to 33.3 % at municipality-level. Herds where other than Pure-Holstein breeds were predominant (i.e. Jersey, Jersey crossbreeds) were more likely to be MAP-qPCR positively infected than those on which where pure-Holstein cattle was predominant (OR=3.7; 95 % CI: 1.1-15.2). The present study reports MAP prevalence in dairy herds in the province of Antioquia (Colombia), and the association between MAP environmental positivity with the predominant breed in the herd.